2002
DOI: 10.5194/angeo-20-981-2002
|View full text |Cite
|
Sign up to set email alerts
|

A first approach to model the low-frequency wave activity in the plasmasphere

Abstract: Abstract.A comprehensive empirical model of waves is developed in the objective to simulate wave-particle interactions involved in the loss and acceleration of radiation belt electrons. Three years of measured magnetic wave field components from the Plasma Wave Instrument on board the DE-1 satellite are used to model the amplitude spectral density of the magnetic wave field of each type of emission observed in the equatorial regions of the plasmasphere: VLF transmitter emissions, chorus emissions, plasmaspheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 47 publications
10
27
0
Order By: Relevance
“…1 clearly demonstrate that the spectral density of magnetosonic waves is concentrated within 5-7 • MLat from the magnetic equator which is consistent with earlier findings (e.g. André et al, 2002;Santolík et al, 2004). It has to be mentioned that the MLT distribution of equatorial magnetosonic emissions became a subject of long-term controversy.…”
Section: Magnetosonic Wavessupporting
confidence: 80%
See 2 more Smart Citations
“…1 clearly demonstrate that the spectral density of magnetosonic waves is concentrated within 5-7 • MLat from the magnetic equator which is consistent with earlier findings (e.g. André et al, 2002;Santolík et al, 2004). It has to be mentioned that the MLT distribution of equatorial magnetosonic emissions became a subject of long-term controversy.…”
Section: Magnetosonic Wavessupporting
confidence: 80%
“…Original paper by Thorne et al (1973) suggested that plasmaspheric hiss can be found at all MLT, and few recent studies (e.g. André et al, 2002;Meredith et al, 2004;Green et al, 2005) have demonstrated that these waves occur primarily on the day side with maximum intensities in the post-noon MLT sector which is consistent with the distributions presented here. Relatively high spectral densities that are seen in Fig.…”
Section: Plasmaspheric Hisssupporting
confidence: 78%
See 1 more Smart Citation
“…Later observations (Gurnett, 1976;Perraut et al, 1982;Laakso et al, 1990;Kasahara et al, 1994;André et al, 2002) revealed that the equatorial noise occurs at radial distances between 2 and 7 R E , and at latitudes within 10 • from the magnetic equator, and that its lowest frequency could go down to the fundamental f H + . Detailed time-frequency spectrograms (Gurnett, 1976) also showed that, what appears as a noise band in the low resolution data, is in fact a superposition of many spectral lines with different frequency spacings.…”
Section: Introductionmentioning
confidence: 99%
“…These emissions are, together with the whistler mode chorus, among the most intense electromagnetic waves observed in the low-latitude region of the Earth's magnetosphere, and their sensitivity to the variations of the geomagnetic activity indicates their importance for the "space weather" applications, i.e. prediction of fluxes of energetic particles as a consequence of variations of the solar input (André et al, 2002). Therefore, we focus our attention on the probability densities of the wave intensity in both electric and magnetic components.…”
Section: Introductionmentioning
confidence: 99%